HYPOGONADOTROPIC HYPOGONADISM (REVIEW) - E.V. Uvarova; E.V. Trifonova (Педиатрическая фармакология)
The review is dedicated to the problem of hypogonadotropic hypogonadism. Modern ideas of the stages of normal sexual development of girls, etiology and pathogenesis of constitutional arrest of sexual development and hypogonadotropic hypogonadism are presented. Modern approaches to the treatment of this condition using hormone replacement therapy and non-hormonal agents are considered.Key words: hypogonadotropic hypogonadism, sexual development arrest, treatment, hormone replacement therapy.